Utility of 3D printed models as adjunct in acetabular fracture teaching for Orthopaedic trainees - S Goyal; CXK Chua; YS Chen; D Murphy; GK O.’Neill (BMC Medical Education, 2022)
Abstract Objective To evaluate the use of 3-D printed models as compared to didactic lectures in the teaching of acetabular fractures for Orthopaedic trainees. Methods This was a randomised prospective study conducted in a tertiary hospital setting which consisted of 16 Orthopaedic residents. Ten different cases of acetabular fracture patterns were identified and printed as 3-D models. The baseline knowledge of orthopaedic residents regarding acetabular fracture classification and surgical approach was determined by an x-ray based pre-test. Trainees were then randomly assigned into two groups. Group I received only lectures. Group II were additionally provided with 3-D printed models during the lecture. Participants were then assessed for comprehension and retention of teaching. Results Sixteen trainees participated in the trial. Both Group 1 and 2 improved post teaching with a mean score of 2.5 and 1.9 to 4.4 and 6 out of 10 respectively. The post test score for fracture classification and surgical approach were significantly higher for 3-D model group (p < 0.05). Trainees felt that the physical characteristics of the 3-D models were a good representation of acetabular fracture configuration, and should be used routinely for teaching and surgical planning. Conclusion 3-D printed model of real clinical cases have significant educational impact compared to lecture-based learning towards improving young trainees’ understanding of complex acetabular fractures.